Hubungan Coping Dengan Kualitas Tidur Pre Operatif Pada Pasien General Anestesi di Ruang Bangsal RSUD Prof. Dr. Margono Soekarjo - Valentina, Aida Nur Dewi; Sebayang, Septian Mixrova; Yudono, Danang Tri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Patients often harbour concerns and fears regarding the surgical process during the preoperative phase, thus developing negative expectations of the final outcome of the procedure. This contributes to patients perceiving surgery as a significant source of excessive stress.Therefore, effective coping strategies are needed to deal with such stressful situations including maintaining a positive mindset, praying, trying to accept the problems that occur, and sharing experiences with others. Coping strategies can overcome poor sleep quality. Poor sleep quality can be caused by various factors, especially in the preoperative context in general anaesthesia patients. The purpose of this study was to determine the relationship between coping and preoperative sleep quality using general anaesthesia at Prof. Dr. Margono Soekarjo Hospital. This study used descriptive correlational method with cross sectional design . The instruments used are the WOC questionnaire (measuring coping) and PSQI (measuring sleep quality). Data analysis in this study used Spearman Rho. The results of this study showed that all respondents used the EFC coping strategy (Emotional Focused Coping) with a percentage value of 100% (85 people), most respondents had poor sleep quality with a percentage value of 81.2% (69 respondents), obtained the results of data analysis p= 0.017 with a significance level of 0.05. This value means p < Sig. which means there is a relationship, so there is a relationship between coping and preoperative sleep quality in general anaesthesia patients in the ward room.